2023
DOI: 10.1002/adhm.202302128
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell‐Derived Mitochondria Enhance Extracellular Matrix‐Derived Grafts for the Repair of Nerve Defect

Jun Bai,
Bingbing Yu,
Chaochao Li
et al.

Abstract: Peripheral nerve injuries (PNI) can lead to mitochondrial dysfunction and energy depletion within the affected microenvironment. The objective is to investigate the potential of transplanting mitochondria to reshape the neural regeneration microenvironment. High‐purity functional mitochondria with an intact structure are extracted from human umbilical cord‐derived mesenchymal stem cells (hUCMSCs) using the Dounce homogenization combined with ultracentrifugation. Results show that when hUCMSC‐derived mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…For the mechanism of mitochondrial treatment, it is possible that mitochondria can be taken up by Schwann cells (SCs) and promote their supportive function in nerve injury repair, indirectly facilitating axonal regeneration. Bai et al have demonstrated that grafts enriched with MSCderived mitochondria effectively treated sciatic nerve defects, confirming the uptake of mitochondria by SCs, which promotes proliferation and migration through enhanced energy synthesis, ultimately leading to axonal regeneration [68]. It will be intreseting to investigate the phenomenon and function of mitochondrial uptake in SCs following the mitochodrial injection therapy in SNI models.…”
Section: Discussionmentioning
confidence: 94%
“…For the mechanism of mitochondrial treatment, it is possible that mitochondria can be taken up by Schwann cells (SCs) and promote their supportive function in nerve injury repair, indirectly facilitating axonal regeneration. Bai et al have demonstrated that grafts enriched with MSCderived mitochondria effectively treated sciatic nerve defects, confirming the uptake of mitochondria by SCs, which promotes proliferation and migration through enhanced energy synthesis, ultimately leading to axonal regeneration [68]. It will be intreseting to investigate the phenomenon and function of mitochondrial uptake in SCs following the mitochodrial injection therapy in SNI models.…”
Section: Discussionmentioning
confidence: 94%
“…In the field of peripheral nerve tissue engineering, acellular allogeneic nerves are typical td-ECM scaffolds. They preserve the native heterogeneous composition and inherent ultrastructure, therefore possessing tissue-specific functionality to some extent [ 24 , 25 ]. Acellular nerve grafts have been widely selected in the treatment of PNI and there are commercially available finished products that have been approved [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%